The Paradox of Diversity: How Critical Race Theory Challenges Conventional Approaches to Equity and Inclusion - Dadang Irawan; Seger Santoso; Mia Christy Patricia (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2024)
This literature review investigates the paradox of diversity by examining how Critical Race Theory (CRT) challenges conventional approaches to equity and inclusion in organizational settings. The study explores the limitations of traditional diversity management frameworks, which often focus on representation or meritocracy without addressing deeper systemic issues of racism and discrimination. By applying CRT's principles of intersectionality and social justice, this review highlights how diversity programs that neglect to confront historical and structural power imbalances may fail to achieve true equity. The findings suggest that CRT offers a more comprehensive approach to understanding diversity, enabling organizations to create strategies that address inequities at their core. However, the review also acknowledges the limitations of applying CRT in diverse global contexts and the challenges organizations may face in implementing these strategies. The study concludes by recommending further empirical research on the outcomes of CRT-based diversity initiatives and suggests expanding the focus beyond race to include other dimensions of diversity such as gender and disability.